Phonetic and phonological cues to prediction: Neurophysiology of Danish stød. (September 2022) - Hjortdal, Anna; Frid, Johan; Roll, Mikael
Highlights: Danish stød, a creaky voice feature, and non-stød can be used predictively. Suffixes invalidly cued by stød/non-stød on word stems led to N400 and P600 effects. Phonological cues associated with stød and non-stød override phonetic cues. Word beginnings with stød have fewer continuations than those with non-stød. The more predictively useful cue, stød, yielded more negative ERP amplitude (PrAN) Abstract: A corpus study and a combined behavioural and neurophysiological study tested how phonetic and phonological features of the Danish creaky voice feature 'stød' influence predictive processing. Being associated with certain word endings, stød and its modal voice counterpart non-stød can cue upcoming speech. Stød has two phases. The first shows phonetic differences in pitch while the second, characterised by creaky voice, has been interpreted as the phonological stød proper. Participants listened to nouns cross-spliced between the two stød phases and between stem and a following singular or plural suffix. Suffixes invalidly cued by phonological stød or non-stød showed longer response times and N400 and P600 effects, the former suggesting that stød/non-stød are becoming grammaticalized as singular and plural morphemes. Even subtle phonetic differences preceding stød proper increased response times, but N400 and P600 amplitudes were not significantly increased. Results suggest predictive use of both phonetic and phonological features, but that phonological stød cues override phonetic cues. The corpus study indicated that word beginnings with stød are less frequent and have fewer possible continuations than non-stød. Stød yielded increased negativity 280–430 ms after stød proper onset, which might be interpreted as a pre-activation negativity for the more predictively useful cue.